Alkylated Benzodithienoquinolizinium Salts as Possible Non-Fullerene Organic N-Type Semiconductors: An Experimental and Theoretical Study - Aracena Astudillo, Andrés Osvaldo.; Caroli Rezende, Marcos.; García, Macarena; Muñoz Becerra, Karina.; Wrighton Araneda, Kerry.; Valdebenito, Cristian; Celis, Freddy; Vásquez, Octavio (MDPI, 2021)
Three photobicyclized benzodithienoquinolizinium tetrafluoroborates (BPDTQBF4) were prepared and evaluated by UV–Vis and fluorescence spectral, electrochemical analysis, and by theoretical calculations as possible organic n-type semiconductors. Evaluation and comparison of their LUMO levels, HOMO-LUMO energy gaps as monomeric and π-stacked dimers with those of other materials, suggest their potential as organic n-type semiconductors. Calculations of their relative charge carrier mobilities confirmed this potential for one derivative with a long (C-14) alkyl chain appended to the polycyclic planar π-system.
Keywords: Benzodithienoquinolizinium cations; Photocyclization of N-Aryl Pyridinium salts; Π-Stacked assemblies; Organic semiconductors